2010
DOI: 10.1371/journal.ppat.1000975
|View full text |Cite
|
Sign up to set email alerts
|

HIV gp41 Engages gC1qR on CD4+ T Cells to Induce the Expression of an NK Ligand through the PIP3/H2O2 Pathway

Abstract: CD4+ T cell loss is central to HIV pathogenesis. In the initial weeks post-infection, the great majority of dying cells are uninfected CD4+ T cells. We previously showed that the 3S motif of HIV-1 gp41 induces surface expression of NKp44L, a cellular ligand for an activating NK receptor, on uninfected bystander CD4+ T cells, rendering them susceptible to autologous NK killing. However, the mechanism of the 3S mediated NKp44L surface expression on CD4+ T cells remains unknown. Here, using immunoprecipitation, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 49 publications
1
86
0
1
Order By: Relevance
“…[20][21][22]38 In these CD4 1 T cells, the cell-surface translocation of NKp44L is mediated through a signaling cascade that involves sequential activation of PI3K, and NADPH oxidase, as well as TC10 inactivation. 39 Saliently, MLL5 has been described as a nuclear protein, 28 whereas NKp44L is not found in the nucleus, consistently with data of Madrid and Ganem. 40 They also showed that during lytic Kaposi's sarcoma-associated herpes virus infection, NKp44L is instead mislocalized and concentrated in the nucleus, whereas its expression on the cell surface decreases, as previously shown in chronic HIV infection.…”
Section: Discussionsupporting
confidence: 80%
“…[20][21][22]38 In these CD4 1 T cells, the cell-surface translocation of NKp44L is mediated through a signaling cascade that involves sequential activation of PI3K, and NADPH oxidase, as well as TC10 inactivation. 39 Saliently, MLL5 has been described as a nuclear protein, 28 whereas NKp44L is not found in the nucleus, consistently with data of Madrid and Ganem. 40 They also showed that during lytic Kaposi's sarcoma-associated herpes virus infection, NKp44L is instead mislocalized and concentrated in the nucleus, whereas its expression on the cell surface decreases, as previously shown in chronic HIV infection.…”
Section: Discussionsupporting
confidence: 80%
“…Shortening the programmed PMN lifespan by abnormally accelerating PMN apoptosis can exacerbate infections (62,63). For example, HIV-1 gp41 induces H 2 O 2 -dependent NKp44L expression on CD4 + T cells, rendering them susceptible to autologous NK killing (31). A better understanding of PMN and NK regulation has the potential to lead to novel immune-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are involved in modulating NK-ligand expression on different targets (30,31) and especially in inducing surface MIC-A/B expression on airway epithelial cells without modifying this ligand's intracellular levels (28). These data strongly suggest that ROS are key mediators in the translocation of NKG2D ligands to the surface of stressed cells that are flagged for death by NK cells.…”
Section: Mic-a Expression On Pmn Surface and Pmn Apoptosis Both Depenmentioning
confidence: 94%
“…An envelope protein of the HIV virus, gp41 is vital for viral entry into target cells (Vieillard et al, 2005). The 3S peptide of gp41 binds to its receptor gC1qR, a receptor for the globular domain of complement component 1q, on CD4 + T cells (Fausther-Bovendo et al, 2010). Binding of the 3S motif to this receptor activates a signaling cascade involving PI3K, NADPHoxidase, Rho-A, and TC10 (Fausther-Bovendo et al, 2010).…”
Section: A Hallmark Of Hiv Infection Is the Progressive Depletion Of Cd4mentioning
confidence: 99%
“…The 3S peptide of gp41 binds to its receptor gC1qR, a receptor for the globular domain of complement component 1q, on CD4 + T cells (Fausther-Bovendo et al, 2010). Binding of the 3S motif to this receptor activates a signaling cascade involving PI3K, NADPHoxidase, Rho-A, and TC10 (Fausther-Bovendo et al, 2010). NKp44L is translocated from the cytoplasm to the plasma membrane and is expressed on the cell surface, where it can bind to NKp44 of activated NK cells.…”
Section: A Hallmark Of Hiv Infection Is the Progressive Depletion Of Cd4mentioning
confidence: 99%